1991
DOI: 10.1002/app.1991.070431109
|View full text |Cite
|
Sign up to set email alerts
|

Application and development of synthetic polymer membranes. VI. Pervaporation of aqueous ethanol solution through quaternized poly[3‐(N′,N′‐dimethyl) aminopropylacrylamide‐co‐acrylonitrile] membranes

Abstract: SYNOPSISMembranes obtained from polymers, quaternized poly [ 3-(N',N'-dimethyl) aminopropylacrylamide-co-acrylonitrile] s, showed selective separation of water from aqueous ethanol solution by pervaporation. The separation factor toward water reached over 15,000. Membrane performance showed a good correlation to membrane polarity. Differential scanning calorimetric melting endotherms of the water-swollen membranes were studied to clarify the state of water in the membranes. The results suggested that there are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…It has been reported that the state of permeant, which is preferentially permeated through a given polymeric membrane, is different from that of bulk permeant; in other words, melting point depression of such a permeant in the membrane is observed in reverse osmosis [12][13][14][15][16][17][18] and pervaporation [19][20][21][22]. The existence of bound water in gelatin was confirmed by 1 H NMR [23] and by thermal analyses [24].…”
Section: Introductionmentioning
confidence: 98%
“…It has been reported that the state of permeant, which is preferentially permeated through a given polymeric membrane, is different from that of bulk permeant; in other words, melting point depression of such a permeant in the membrane is observed in reverse osmosis [12][13][14][15][16][17][18] and pervaporation [19][20][21][22]. The existence of bound water in gelatin was confirmed by 1 H NMR [23] and by thermal analyses [24].…”
Section: Introductionmentioning
confidence: 98%
“…The pervaporation process has been successfully used in the dehydration of alcohols,8, 9 as well as in the removal of dissolved volatile organic compounds from water 10–19. Böddeker and co‐workers investigated the removal of low‐volatility aromatic hydrocarbons [i.e., thymole (MW = 150.2 g/mol) and vanillin (MW = 152.2 g/mol)] from dilute aqueous solutions through polyether‐ block ‐polyamide membranes by pervaporation 11, 12.…”
Section: Introductionmentioning
confidence: 99%